2021
DOI: 10.3201/eid2703.200182
|View full text |Cite
|
Sign up to set email alerts
|

Tropheryma whipplei in Feces of Patients with Diarrhea in 3 Locations on Different Continents

Abstract: We examined fecal specimens of patients with diarrhea from 3 continents for Tropheryma whipplei and enteropathogens. T. whipplei was most common in South Africa, followed by Singapore and Germany. Its presence was associated with the presence of other pathogens. An independent causative role in diarrhea appears unlikely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Similar to previous Korean studies conducted with saliva, T. whipplei was detected low in the stools of patients with diarrhea, with a prevalence of 1.4% [ 22 , 23 ]. A recent study investigating the stools of patients with diarrhea for T. whipplei in three locations on different continents reported that its prevalence may differ between continents [ 26 ]. The prevalence of T. whipplei was 17.5% in South Africa, 15% in Singapore, and 3.3% in Germany, all higher than in Korea [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to previous Korean studies conducted with saliva, T. whipplei was detected low in the stools of patients with diarrhea, with a prevalence of 1.4% [ 22 , 23 ]. A recent study investigating the stools of patients with diarrhea for T. whipplei in three locations on different continents reported that its prevalence may differ between continents [ 26 ]. The prevalence of T. whipplei was 17.5% in South Africa, 15% in Singapore, and 3.3% in Germany, all higher than in Korea [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study investigating the stools of patients with diarrhea for T. whipplei in three locations on different continents reported that its prevalence may differ between continents [ 26 ]. The prevalence of T. whipplei was 17.5% in South Africa, 15% in Singapore, and 3.3% in Germany, all higher than in Korea [ 26 ]. To date, Whipple’s disease has not been reported in Korea, and it has been reported very rarely in Japan [ 23 , 27 , 28 ]; it is in line with the low prevalence of T. whipplei found in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are also in line with a recent work from Ghana in which T. whipplei was found equally in symptomatic pediatric cases and controls [ 25 ]. Despite earlier research indicating that individuals might develop mild diarrhea when infected, Feurle et al concluded in their study of symptomatic patients from different origins that T. whipplei was associated with the presence of other stool pathogens, but that an independent causative role of this sole microbe in diarrhea appeared unlikely [ 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Classic WD is rare, but its cause, T. whipplei , is an intestinal bacterium that is relatively commonly detected in the saliva and stools of healthy carriers [ 4 ]. The prevalence of T. whipplei has been reported to vary from 1.5% to as high as 48% depending on age, region, occupational exposure, and underlying disease [ 4 11 ]. In Europe, T. whipplei was detected at a prevalence of up to 4% in the stools of healthy carriers, but at a higher prevalence of 12–25% in the stools of sewer workers and patients with liver cirrhosis [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%